1983
DOI: 10.1083/jcb.97.4.1303
|View full text |Cite
|
Sign up to set email alerts
|

Golgi membranes contain an electrogenic H+ pump in parallel to a chloride conductance.

Abstract: Rat liver Golgi vesicles were isolated by differential and density gradient centrifugation. A fraction enriched in galactosyl transferase and depleted in plasma membrane, mitochondrial, endoplasmic reticulum, and lysosomal markers was found to contain an ATP-dependent H + pump.This proton pump was not inhibited by oligomycin but was sensitive to N-ethyl maleimide, which distinguishes it from the F0-F1 ATPase of mitochondria. GTP did not induce transport, unlike the lysosomal H + pump. The pump was not dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(138 citation statements)
references
References 22 publications
9
127
2
Order By: Relevance
“…Bars, 200 nm. ATPases and ion exchangers [Glickman et al, 1983;Al Awqati, 1995;Demareux et al, 1998;Thompson et al, 2002;Nakamura et al, 2005]. Therefore, we examined whether the actin toxin-induced alterations of Golgi cisternae ultrastructure were accompanied by changes in intra-Golgi pH (pH G ).…”
Section: Depolymerization But Not Stabilization Of F-actin Raises Intmentioning
confidence: 99%
“…Bars, 200 nm. ATPases and ion exchangers [Glickman et al, 1983;Al Awqati, 1995;Demareux et al, 1998;Thompson et al, 2002;Nakamura et al, 2005]. Therefore, we examined whether the actin toxin-induced alterations of Golgi cisternae ultrastructure were accompanied by changes in intra-Golgi pH (pH G ).…”
Section: Depolymerization But Not Stabilization Of F-actin Raises Intmentioning
confidence: 99%
“…6.5 for cisternae of the trans-Golgi [107]. Such acidification is due to the activity of an ATP-dependent proton pump [108][109][110], and is most certainly important for preserving TGN function as a whole [111,112].…”
Section: Sorting Of Proteins Destined For the Regulated Secretory Patmentioning
confidence: 99%
“…Proton-translocating ATPases have also been described in a number of intracellular organelles (Anderson et al, 1982;Hutton, 1982;Dean et al, 1984;Forgac et al, 1983;Galloway et al, 1983;Glickman et al, 1983). Intracellular vesicles with proton pumps fuse with and form from the plasma membrane, and it has been suggested that H+ pumps may participate in cellular pH regulation (Adelsberg & Al-Awqati, 1986).…”
Section: H+-translocating Atpasesmentioning
confidence: 99%